Requirement Analysis of Project-based Thematic Teaching Material Design as An Effort of Character Education Reinforcement - Manggalastawa, Manggalastawa; Susilaningsih, Endang; Wardani, Sri (Journal of Primary Education, 2019)
The purpose of this research was to analyze the need for project-based thematic teaching material design as an effort of character education reinforcement for elementary students grade IV. This research used mixed methods by using the model of sequential exploratory strategy. Data analysis technique of this study was qualitative and quantitative analysis. The first step was a qualitative method and then measuring result using tools or certain instrument by using the quantitative method. The analysis of this study consists of qualitative analysis by using resource triangulation technic and quantitative descriptive analysis. The result of this study showed that (1) teacher, principal, and students need teaching materials design based on teaching materials feasibility aspect that was content, presentation, language, and graphics. Project-based thematic teaching materials design as an effort to the character education reinforcement of mutual cooperation appropriate with the competency claim in the sub-theme teaching lesson. (2) Validation result of teaching materials design showed the average score from three validators was 35.67 with very good criteria. In general, validation result from the three validators stated that project-based thematic teaching materials design was proper to be used.